Animal Activism and the Zoo-Networked Nation - Vandersommers, Daniel (Humanimalia, 2015)
The first American zoos commanded the attention of early animal activists around the turn of the twentieth century. This essay argues that all zoogoers in the first zoos took part in popularizing a discourse about both animal welfare and “animal rights.” This essay also posits that as zoos were networked together, so were their accompanying “activists.” As zoos became a centerpiece of the American city, they simultaneously established public forums for the rethinking of animals.